Women in Peacebuilding: Afghan Women’s Struggles Against Intersectional Oppression during Peace Negotiations - Akhmady, Fajarningrum; Rahmawati, Nursabrina; Krisnamukti, Tedy Asjad (Pusat Studi Gender Universitas Jember, 2026)
The drastic changes in Afghanistan's social and political structure following the Taliban's takeover of the government in 2021 have resulted in severe oppression of women. The reimplementation of discriminatory policies has created significant challenges for Afghan women in fighting for their rights. This study aims to analyze women's struggles within the context of peace negotiations, not only in the Doha Agreement between the United States and the Taliban; which failed to address women’s rights, but also in the subsequent intra-Afghan negotiations between the Taliban and the Afghan government, where women continued to face structural barriers to meaningful participation. Using a postcolonial feminist approach, this research explores the concept of